Ultra-wideband transmission line bandpass filters with sharpened roll-off skirts - Quek, Alwyn Chiao Liang (2009)
A multiple mode resonator is proposed to form an ultra-wideband (UWB) bandpass filter (BPF). The design consists of a ring resonator in the middle connected by interdigital coupled lines fed from both sides of the network. This ring resonator is studied to relocate its first four resonant modes within the 3.1 to 10.6 GHz passband, whereas placing the fifth resonant mode at the coupling transmission zero of the interdigital coupled lines that drive this MMR at both sides of the network. Meanwhile, the sixth resonant mode is being suppressed by placing four open circuit stubs at the four corners of the ring resonator to generate transmission zero at the desired frequency. Finally, a modified UWB bandpass filter is proposed with sharpened roll-off skirts outside the UWB passband on both sides, widened upper-stopband and lowered loss in the passband. After optimization the proposed MMR UWB filter was fabricated on a RT Duroid 6010. The measured results demonstrated that the insertion loss is lower than 1.0dB in the desired UWB passband (e.g. 3.1 to 10.6 GHz) and higher than 18.0dB in the upper-stopband (11.2 to 20 GHz), while the group delay varies between 0.15 to 0.65 ns. The measured results are in reasonable agreement with the simulated results thus confirms the actual realization of a MMR UWB filter.